2011
DOI: 10.33549/physiolres.932092
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Effects of Central Hydrogen Sulfide Are Related to KATP Channels Activation

Abstract: Hydrogen sulfide (H2S), an endogenous “gasotransmitter”, exists in the central nervous system. However, the central cardiovascular effects of endogenous H2S are not fully determined. The present study was designed to investigate the central cardiovascular effects and its possible mechanism in anesthetized rats. Intracerebroventricular (icv) injection of NaHS (0.17~17 μg) produced a significant and dose-dependent decrease in blood pressure (BP) and heart rate (HR) (P<0.05) compared to control. The higher dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Systemic administration of H 2 S donors and precursors decreased mean arterial pressure (MAP) in various models of hypertension [ 10 13 ]. Nevertheless, mediation of H 2 S in the cardiovascular center has been controversial [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic administration of H 2 S donors and precursors decreased mean arterial pressure (MAP) in various models of hypertension [ 10 13 ]. Nevertheless, mediation of H 2 S in the cardiovascular center has been controversial [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In different types of cells, including neurons, vascular smooth muscle cells, cardiomyocytes, and pancreatic b-cells, H 2 S stimulates the activity of the adenosine triphosphate-sensitive potassium channels. [17][18][19] In the central nervous system, H 2 S attenuates the neuroinflammatory processes induced by lipopolysaccharide (LPS) 20 and amyloid-b. 21 It suppresses oxidative stress induced by hydrogen peroxide, 22 and protects cells against the neurotoxins rotenone 23 and 6-hydroxydopamine.…”
mentioning
confidence: 99%
“…Furthermore, it has been recently demonstrated that the enzyme CBS is expressed in the PVN (101). Accordingly, H 2 S has been shown to participate in the hypothalamic control of heart rate and blood pressure (27,67), body temperature during hypoxia (64), and corticotropin-releasing hormone (CRH) release (29).…”
Section: Figure 3 Overview Of Nitric Oxide (No) Effects On Magnocellmentioning
confidence: 99%